Sertu cleansing technique from four schools of jurisprudence and it’s requirements in Malaysia - Awang, Mohd Daud; Mohd Zaki, Nor Nadiha (Universiti Islam Pahang Sultan Ahmad Shah, 2022)
Cleanliness is an important part of life, and Islam has provided a guideline on how to cleanse an extreme najs (najs mughallazah). Sertu is a terminology to indicate the process of purifying najs mughallazah. Different mazhab have a distinctive understanding and procedure on how to cleanse these najs, but the importance of cleaning the najs is agreed upon by all. Soil is an important component in the sertu process and is investigated to prove its effectiveness in cleansing the harmful contaminant and washing the filth. Therefore, this paper aims to discuss the reason the soil is used in the cleaning process for the mughallazah najs from a scientific perspective. This matter is very important to understand due to most halal products being produced in non-Muslim countries and making the sertu process a crucial factor in the Halal industry. An R&D initiative is done and closely linked to the sertu procedure of halal logistics in order to fulfil the end users' demand for reliable halal status. Therefore, it is important to understand not only the concept of sertu from shariah but also from the scientific perspective because it will benefit to Halal industry in developing a standard procedure for sertu cleansing technique.